The ideal-based zero-divisor graph of commutative chained rings - Anderson, David F.; Atani, S. Ebrahimi; Kohan, M. Shajari; Sarvandi, Z. Ebrahimi (Sarajevo Journal of Mathematics, 2024)
Let I be a proper ideal of a commutative ring R with 1 eq 0. The ideal-based zero-divisor graph of R with respect to I, denoted by Γ_I(R), is the (simple) graph with vertices { xR I xy I for some y RI }, and distinct vertices x and y are adjacent if and only if xy I. In this paper, we study Γ_I(R) for commutative rings R such that R/I is a chained ring.